The impact of population agglomeration in urban agglomerations on green total factor productivity: insights from China - Zhang, Songlin; Ding, Jia; Ji, Chunli; Shao, Qing; Chen, Weihong (Frontiers in sustainable cities, 2025)
Enhancing Green Total Factor Productivity (GTFP) is crucial for achieving sustainable development goals. While existing studies have largely focused on the impact of city-specific factors on GTFP, the influence of factors at the urban agglomeration scale has been overlooked. Given the ongoing trend of population agglomeration in urban agglomerations, the role of cross-city population agglomeration dynamics at the urban scale has become increasingly significant. This study investigates the impact and mechanisms of population agglomeration in urban agglomerations on GTFP, using panel data from 282 prefecture-level and above cities in China spanning the period 2011-2022. The findings indicate that population agglomeration in urban agglomerations can improve GTFP. Mechanism analysis reveals that population agglomeration in urban agglomerations enhances GTFP by strengthening knowledge spillover effects, increasing market potential, and promoting the upgrading of the human capital structure. Further research shows that when population agglomeration in urban agglomerations reaches a certain scale, a unified functional network can be formed within the urban agglomeration, leading to a more substantial increase in GTFP. Heterogeneity analysis suggests that the positive impact of population agglomeration in urban agglomerations on GTFP varies across different cities. Specifically, such agglomeration improves GTFP more effectively in central cities than in peripheral cities; this effect is significant in the southeast region, in cities with stronger environmental regulation, and resource-based cities, but is insignificant in the northwest region, in cities with weaker environmental regulation, and non-resource-based cities. These findings provide novel policy pathways for cultivating urban agglomerations as engines of green economic transformation in an era of escalating spatial population agglomeration.